2006
DOI: 10.1111/j.1365-2265.2006.02454.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term dehydroepiandrosterone treatment increases platelet cGMP production in elderly male subjects

Abstract: This study shows that short-term treatment with DHEA increased platelet cGMP production, a marker of NO production, in healthy elderly subjects. This effect is coupled with a decrease in PAI-1 and LDL cholesterol levels as well as an increase in testosterone and E(2) levels. These findings, therefore, suggest that chronic DHEA supplementation would exert antiatherogenic effects, particularly in elderly subjects who display low circulating levels of this hormone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…Several clinical and population-based studies suggest that DHEAS plays a protective role against atherosclerosis and coronary artery disease in men (42,43). One study found that chronic DHEA supplementation exerts anti-atherogenic effects although homocysteine concentrations were not modified by the treatment (44). It seems likely that the anti-atherogenic effects of DHEAS are independent of its action on plasma homocysteine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical and population-based studies suggest that DHEAS plays a protective role against atherosclerosis and coronary artery disease in men (42,43). One study found that chronic DHEA supplementation exerts anti-atherogenic effects although homocysteine concentrations were not modified by the treatment (44). It seems likely that the anti-atherogenic effects of DHEAS are independent of its action on plasma homocysteine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…cGMP, which serves the role of acetylcholine, is widely distributed in various tissues. Previous studies (25,26) demonstrated that the cGMP is positively correlated to DHEAS. The present study additionally demonstrated that the cGMP level in the PCOS subgroup 1 was elevated compared with the control group.…”
Section: Discussionmentioning
confidence: 84%
“…In elderly subjects, physiological doses (50 mg p.o. daily) and long-term administration (for 2 months) of DHEA induced an increase in platelet cGMP levels, as a marker of nitric oxide production, which may suggest a possible antiatherogenic effect of this steroid in physiological concentrations [187].…”
Section: Studies Using Ex Vivo Platelet Function Assaymentioning
confidence: 94%